(untitled) (Indian Journal of Animal Production and Management, 2013)
A diagnostic study was conducted in Nalgonda district of Andhra Pradesh with a sample size of 270 sheep farmers. The results indicated that there was a 73.46 per cent increase in overall knowledge of the shepherds after exposure to training programmes. There was a 29.78 per cent change in the attitude of shepherds who underwent training on scientific sheep rearing practices. Combination of different teaching methods (TV + Charts and Posters + Lecture method + Exposure visit) was effective in imparting the knowledge to the shepherds. The trainings formulated based on the needs of the shepherds revealed a positive indication of adoption of scientific sheep rearing practices.